Institutions, agency and the institutionalization of budgetary control in a hybrid state-owned entity - Gooneratne, T.N.; Hoque, Z. (Elsevier Publishing, 2016)
In this paper we develop an understanding of the roles played by external institutional forces and organizational entrepreneurs acting as agents in the institutionalization of the budgeting system within a hybrid state-owned entity. Drawing upon the notions of external institutions and agency of institutional entrepreneurs within institutional theory, we investigated this phenomenon using data from field-interviews, observations and archival documents. Our analysis of the findings suggests that the institutionalization of the budgeting system in a hybrid entity is materialized amid external institutional influences, deliberations of key organizational agents, and more importantly the idiosyncrasies in the competitiveness and complexity of the particular industry and the organizational setting. We contribute to the current body of literature on institutionaliza tion of management control techniques at the practice level and management control in hybrid entities.
Keywords: Critical; Public sector; Management control; Budgeting; External institutions; Agentic institutionalism; Hybrid organization